Analysis of customer queuing at hydrogen stations. (5th May 2022) - Brown, Tim; Kisting, Hilary
Abstract: An analysis is presented of service rates at nineteen retail hydrogen stations in a heavily-used California network to gain insight into station capacity impacts on customer wait times. Each station has only one fueling position resulting from just one, one-sided dispenser. Collected data of each refueling step for 1000's of hydrogen refuelings in California provides insight into station and network capacity for both California and emerging infrastructure elsewhere. The analysis herein concludes that customers would be exponentially better served with a network of larger, multi-position stations instead of smaller, one position stations. Highlights: Diurnal profiles and hourly service rates for hydrogen fueling well-match those of gasoline fueling. Refueling time data is aggregated and presented for 1, 000s of retail hydrogen transactions. Actual time spent refueling for hydrogen customers is substantially higher than those for gasoline. Most H2 stations have a single fueling position compared to multiple hoses available at gasoline stations. Modeling and field data quantify the reduction in customer wait times for stations having multiple fueling positions.